Microstructure Characteristics and Mechanical Properties of Grey Cast Iron at Varied Ferrosilicon Addition - Kutelu, Bolarinwa Johnson; Oluyori, Raymond Taiwo; Omoyeni, Dada Oluwadare (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
Inoculation is an essential metallurgical route for controlling solidification conditions of cast iron, consequently, in this study, the influence of varied percent ferrosilicon (FeSi) addition on microstructure and mechanical properties of grey cast iron (GCI) was investigated. A 50Kg capacity rotary furnace was used to melt the charge (Auto engine block scrap, graphite, ferrosilicon (FeSi) and limestone). The casting was produced in a greensand mold with wooden rectangular pattern of length 50 mm and breadth 30 mm. Chemical compositions and carbon equivalent values (CEVs) of the samples were determined, using Optical emission spectrometry (AR 4 metal analyzer) and the expression respectively. Microstructures of the samples were obtained, using metallurgical microscope (model number NJF-120A). The tensile and hardness properties were measured, using Universal tensile tester and Rockwell hardness tester respectively. From the results, C and Si were the major elements. Other trace elements were Mn, P, S and Al. CEVs of both the control and inoculated samples were less than 4.3%. Microstructure of the control sample was comprised of primary dendrites and graphite flakes, while those of the inoculated samples were characterized by varied amount of more developed primary dendrites, longer graphite flakes and austenite dendrites. Also, a number of small MnS particles were observed in relative amount within the microstructures. Tensile and hardness properties of the FeSi inoculated samples were superior to the control sample. Highest tensile strength and hardness values of 76.62 MPa and 99.89 HRB respectively were obtained at the optimum inoculation of 1.5 wt. % FeSi.